Transforming Writing Education: An Investigation of Students' Experiences with Project-Based Learning in Teaching Writing: English - Ratu, Donal Matheos; Nurhayati , Nurhayati; Ratni, Ni Putu; Nurmaisyah, Nurmaisyah; Rantung, Ruly; Kojongian, Prilimercy Lingkan; Tatipang, Devilito Prasetyo (LPPM Universitas Lancang Kuning. Pekanbaru. Indonesia, 2025)
In response to the pedagogical shift toward more authentic and student-centered learning in higher education, this study investigates the integration of Project-Based Learning (PjBL) in teaching academic writing to English education students in Indonesia. While PjBL has been recognized for fostering collaboration and critical thinking, limited research has explored how students behaviorally, emotionally, and cognitively respond to its implementation in writing instruction. Addressing this gap, a qualitative case study was conducted involving twenty university students who participated in a semester-long PjBL-based writing course. Drawing on data from observations, interviews, and document analysis involving twenty English education students, this study reveals three key findings. Behaviorally, students demonstrated active participation, leadership, and collaborative responsibility, supported by structured peer roles and group accountability mechanisms, although a few exhibited passive involvements due to unequal workload distribution. Emotionally, most students experienced enthusiasm and a sense of accomplishment, particularly during topic selection and final submission, but some expressed anxiety related to public presentation and frustration over imbalanced team contributions. Cognitively, students showed marked improvements in brainstorming, organizing arguments, and revising drafts, guided by visual tools, feedback, and reflective journaling, which enhanced their critical thinking and writing cohesion. These findings highlight PjBL as a transformative pedagogy that fosters technical skills, autonomy, emotional resilience, and cognitive engagement. By offering an integrated view of students’ experiences, the study advocates for strategies that support collaboration, emotional support, and metacognitive awareness in academic writing, with broader implications for advancing student-centered learning in higher education.